Cholera, Shigellosis and Salmonellosis Incidence Among the People of some Districts of Nepal - Shah, Binod Kumar; Sharma, Sapana; Shakya, Gita; Upadhyay, Bishnu Prasad (Nepal Journal of Science and Technology, 2013)
Diarrhoea is a major health problem throughout the world, and responsible for high morbidity and mortality in Nepal. The cross-sectional prospective study was carried out to determine the incidence of Cholera, Shigellosis and Salmonellosis with screening of possible extended spectrum â-lactamase producers from 268 diarrhoeal stool samples from Nepalgunj area and different hospitals of Nepal during April 2010 to January 2011. The specimens were processed by standard microbiological methods and the casual organisms confirmed with serology. Altogether 14.18% of bacterial incidence was found with 8.21% incidence of Vibrio cholerae O1, 2.24% of Shigella spp. and 3.73% of Salmonella spp. All isolated Vibrio cholerae O1 were El Tor Ogawa and all Shigella spp. were Shigella flexneri B. Highest bacterial culture positivity (47.36%) were observed in Kathmandu while highest V. cholerae isolation (77.27%) was observed in Nepalgunj. The highest number of Salmonella spp. and Shigella spp. were isolated from Kanti Children’s Hospital. Highest bacterial culture positivity (47.36%) and highest isolation of V. cholerae (81.81%) were observed in August. The bacterial culture positivity was significantly associated with places and months (p <0.05). However, there was no statistical difference in the bacterial culture positivity with sex (P >0.05). 100% Vibrio cholerae, 100% Shigella spp. and 80% Salmonella spp. were multi-drug resistant. Only one Salmonella Cholerasuis was extended spectrum â-lactamase producer. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 165-172 DOI: http://dx.doi.org/10.3126/njst.v13i1.7455